2021
DOI: 10.1108/bfj-04-2021-0358
|View full text |Cite
|
Sign up to set email alerts
|

Relationships, sustainability and agri-food purchasing behaviour in farmer markets in Italy

Abstract: PurposeThe study aims to demonstrate that farmers' markets can represent a model of environmental, social and governance reference for modern agri-food systems facing the challenge of post COVID-19 pandemic reconstruction, responding to consumer expectations in terms of health, safety and wholesomeness of agri-food products.Design/methodology/approachA sample of consumers was surveyed in farmers' markets and social network analysis (SNA) was adopted as a methodological approach to reconstruct the links between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Previous studies have typically identified the proportion of female buyers at FMs as between 50 and 75% (Abelló et al, 2013; Aguirre, 2007; Anderson et al, 1996; Azavedo and Walsh, 2019; Berg and Preston, 2017; A6). Less female participation is found in only a few cases (Foti and Timpanaro, 2021; Schneider and Francis, 2005; Shakeel Ul and Selvaraj, 2013; Solanki and Inumula, 2021), in proportions of 43.7% (Foti and Timpanaro, 2021) and 44.8% (Ashtab and Campbell, 2021). Generally, Asian FMs are associated with fewer female shoppers, ca.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have typically identified the proportion of female buyers at FMs as between 50 and 75% (Abelló et al, 2013; Aguirre, 2007; Anderson et al, 1996; Azavedo and Walsh, 2019; Berg and Preston, 2017; A6). Less female participation is found in only a few cases (Foti and Timpanaro, 2021; Schneider and Francis, 2005; Shakeel Ul and Selvaraj, 2013; Solanki and Inumula, 2021), in proportions of 43.7% (Foti and Timpanaro, 2021) and 44.8% (Ashtab and Campbell, 2021). Generally, Asian FMs are associated with fewer female shoppers, ca.…”
Section: Resultsmentioning
confidence: 99%
“…The residence of FM shoppers is typically the same municipality as the FM itself (Abelló et al, 2013; Chen, Yu and Fu, 2021; Dukeshire et al, 2010; Feagan, Morris and Krug, 2004; Foti and Timpanaro, 2021; A13). FMs are visited mainly by residents of small and large cities (Bavorova, Unay-Gailhard and Lehberger, 2016; González, 2009; Pisarn, Kim and Yang, 2020; Spilkova, 2018; Spilková, Fendrychová and Syrovátková, 2013; A14), probably because in smaller municipalities (e.g., townships), fruit and vegetable are often grown locally or at home, so residents are less in need of FMs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It should further be pointed out that the two studies were conducted before the COVID-19 pandemic. This global event could have influenced the beliefs (Dudek and Śpiewak, 2022; Foti and Timpanaro, 2021; George and Nair, 2022) which determine ATTs, SN and PBC (e.g. De Leeuw et al ., 2015; La Barbera and Ajzen, 2020b) which, in turn, can influence ethical purchasing intentions.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%